Aspects of the teacher’s activity for the prevention and overcoming of students’ learning difficulties - Мурзалинова, Алма; Жанбеков, Хайрулла; Корнилова, Татьяна; Галимжанова, Маржан; Байдалиев, Дархан (Pedagogy and Psychology, 2022)
The article presents recommendations on the effective activity of the teacher regarding the achievement of personal, system-activity, subject results, the organization of work with underachieving students. The work plan with the underachievers is illustrated, which reflects not only the individual work of the teacher, but also the system of work of the teaching staff to replenish the knowledge, skills, competencies of students. The necessity of taking into account physiological, age, psychological, cognitive, social factors of low academic performance and academic failure is considered. The ability of self-organization and independent work is noted, replenishing training is updated. This article was prepared within the programme trust fund study OR 11465474 «Scientific foundations of modernization of the education system and science» (2021-2023, National Academy of Education named after Y.Altynsarin). The author’s group thanks the Ministry of Science and Higher Education of the Republic of Kazakhstan for the opportunity to publish this article.